Peran Mahasiswa Dalam Pengembangan Agrowisata: Wisata Edukasi di Pusat Penelitian Perkebunan Gula Indonesia (P3GI) - Nisa Hafi Idhoh Fitriana; Maysaroh Tri Khusnah; Nia Amalia; Rachmawan Arifianto; Danang Permadhi (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2024)
The Indonesian Sugar Plantation Research Center (P3GI) serves as a research institution for sugar in Indonesia and also offers educational tours as a medium to educate the Indonesian public. However, during the operation of these educational tours, several evaluations have been identified that have led to visitors feeling less satisfied and comfortable during their visits. The evaluations focused on social media as a marketing tool and the lack of photo and educational spots in the P3GI area. The purpose of these developments is to help improve the evaluations that have arisen in the educational tours to make them better. The results of these developments include the creation of engaging content for social media related to the educational tours and the establishment of a sweetener garden as a way to add more photo and educational spots for visitors, as well as the distribution of surveys to monitor evaluations of P3GI's educational tours.